Aportes de las estrategias metacognitivas al nivel de comprensión lectora inferencial (2021)
The purpose of this research was to establish the contributions of the use of Metacognitive Strategies at the level of Inferential Reading Comprehension in 5th grade students of the IED El Carmen, from the city of Santa Marta. The population universe was made up of 1014 students, from socioeconomic strata 0, 1 and 2, with a population of 380 elementary school students between the ages of 9 and 11, and a non-probabilistic sample of 33 students. A non-experimental field research with a mixed nature approach was projected, following the post-positivist paradigm. The standardized Evaluate to Advance test designed by ICFES (2020) was applied, and the Inventory of Metacognitive Skills MAI, designed by Schraw & Sperling (1994) and validated by Huertas, Vesga, and Galindo (2014); implemented in the current classroom space (Remote Education Model). Quantitative and qualitative results were obtained by means of which it was possible to establish that the contributions of Metacognitive Strategies at the level of Inferential Reading Comprehension in 5th grade students had a greater representation in the Organization, Monitoring and Planning strategies with a predominance of Declarative inferences and Macrostructural, with a positive correlation between the two variables: Metacognitive Strategies and Inferential Reading Comprehension.